METHOD OF DETERMINING AIS/MAIS TRAUMA SCORE FROM ICD 10 DIAGNOSIS CODES - Anđelić, Slađana Lj; Kukic, Dragoslav; Markovic, Marković; Strbac, Mirjana; Rajcevic, Smiljana; Colakovic, Goran (Halo 194 Scientific Journal of Emergency Medicine, 2024)
The group of high representatives of European Union (EU) member states for traffic safety published in 2013 a new definition of severe trauma (TT) caused by traffic accidents. According to this definition, TT in road traffic are non-fatal injuries with a Maximum Abbreviated Injury Scale (MAIS) of 3 and above. Since 2014, the Recommendation at the EU level has been in effect to use the Abbreviated Injury Scale (AIS) for the assessment of injuries in traffic accidents, and MAIS 3+ for serious injuries. The previous experiences of countries that record injuries based on the MAIS 3+ classification system have shown its high validity and reliability of the collected data, reducing the risk of making arbitrary conclusions and subjective assessment of the severity of the injury, as well as the risk of inadequate reporting. MAIS 3+ enables better and more complete collection of data on traffic accidents at the national and international level, enables international comparability of data and the creation of adequate preventive activities. The tendency is that in the coming period, all EU member states will collect data on serious bodily injuries according to this definition.
Keywords: severe trauma, traffic accidents, AIS, MAIS, ICD